2011
DOI: 10.1007/s10853-011-5724-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon nanotubes on the fracture toughness and fatigue performance of a thermosetting epoxy polymer

Abstract: Multi-walled carbon nanotubes, with a typical length of 140 lm and a diameter of 120 nm, have been used to modify an anhydride-cured epoxy polymer. The modulus, fracture energy and the fatigue performance of the modified polymers have been investigated. Microscopy showed that these long nanotubes were agglomerated, and that increasing the nanotube content increased the severity of the agglomeration. The addition of nanotubes increased the modulus of the epoxy, but the glass transition temperature was unaffecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
163
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(181 citation statements)
references
References 59 publications
15
163
3
Order By: Relevance
“…A clear reduction in the KIC with the incorporation of CNTs was obtained, contrary to other studies [9,11,26]. An analysis of the fracture surfaces, as summarized in Figure 1, indicates a smooth fracture surface for the neat resin (a) and a rougher surface of the CNT reinforced resins, as shown in (b).…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…A clear reduction in the KIC with the incorporation of CNTs was obtained, contrary to other studies [9,11,26]. An analysis of the fracture surfaces, as summarized in Figure 1, indicates a smooth fracture surface for the neat resin (a) and a rougher surface of the CNT reinforced resins, as shown in (b).…”
Section: Resultscontrasting
confidence: 65%
“…The reduced moduli, obtained by nanoindentation and the results of the tensile and shear tests, show no significant changes (less than 3% of variation) with CNT incorporation. Despite the fact that several articles [6][7][8][9][10][11]26] indicated an enhancement of the mechanical properties of polymeric resins by the incorporation of CNTs, it should be noted that the epoxy resin used in this work has a high stiffness compared to other related research studies. This is in agreement with previous studies by Ci and Bai [6] who concluded that the resin stiffness decreases the potential positive effect of CNTs.…”
Section: Resultsmentioning
confidence: 74%
“…For both the HalpinTsai and Mori-Tanaka models, the aspect ratio is the factor that has the most significant effect on the composite modulus predicted. The models can be modified to take into account the reduction in aspect ratio [53], however the introduction of such constants tend to be strictly systematic and changes depending on the system used. The Halpin-Tsai and Mori-Tanaka "parallel" models were relatively close in value, however there were more deviations in the "random" arrangement as the concentration is increased.…”
Section: Young's Modulusmentioning
confidence: 99%
“…The measured values of G i ranged from 4 to 70 J/m 2 , comparable to other fibre reinforced polymers. For the current study, a value of G i = 25 J/m 2 was used [53]. For the platelet pull-out mechanism:…”
Section: Fracture Energymentioning
confidence: 99%
“…[1][2][3][4][5] The properties of CNTs could be chemically modified by addition of halogens, as fluorine. [6][7][8][9] Some authors have reported that the functionalization of CNTs with fluorine significantly changes their electrical, mechanical and optical properties.…”
Section: Introductionmentioning
confidence: 99%